<span>6x2 -5x –3 = 0
a = 6 b=-5 and c=-3
x = [-b +-sq root (b² -4ac)] / 2a
x = [--5 +-sq root (25 -4*6*-3)] / 2*6
x = [5 +- sq root (25 +72)] / 12
x = [5 +- sq root (97)] / 12
x1 = [5 + </span><span><span><span>9.8488578018
</span>
</span>
</span>
] / 12
x1 =
<span>
<span>
<span>
14.8488578018
</span>
</span>
</span>
/ 12
x1 =
<span>
<span>
<span>
1.2374048168
</span>
</span>
</span>
x2 = [5 -
<span>
<span>
<span>
9.8488578018
</span>
</span>
</span>
] / 12
x2 =
<span>
<span>
<span>
-4.8488578018
</span>
</span>
</span>
/ 12
x2 =
<span>
<span>
<span>
-0.4040714835
</span>
</span>
</span>
6 / 1/2
that's 6 * 2
There are 12 meals in a bag of dog food
Hi hi I am going to call you tomorrow and I will call you tomorrow morning I know you’re doing good
i believe it would be 5.25
12-5=7
7*12=84
84/ 16 = 5.25
i hope this helps
The expression of the mathematical statement given as "Jaun's age, x, is 4 times his age 15 years ago" is x = 4 * (x - 15)
<h3>How to rewrite the statement as an expression?</h3>
The mathematical statement is given as
Jaun's age, x, is 4 times his age 15 years ago
From the statement, we have:
x represent Juan's current age
This means that his age 15 years ago is
15 years ago = x - 15
4 times his age 15 years ago is
4 * 15 years ago = 4 * (x - 15)
The above equation is equivalent to his current age
So, we have
x = 4 * (x - 15)
Hence, the expression of the mathematical statement given as "Jaun's age, x, is 4 times his age 15 years ago" is x = 4 * (x - 15)
Read more about expressions at
brainly.com/question/2972832
#SPJ1